2020
DOI: 10.25259/sni_547_2020
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic endonasal skull base surgery during the COVID-19 pandemic: A developing country perspective

Abstract: Background: Although primarily a respiratory disorder, the coronavirus pandemic has paralyzed almost all aspects of health-care delivery. Emergency procedures are likely continuing in most countries, however, some of them raises certain concerns to the surgeons such as the endoscopic endonasal skull base surgeries. The aim of this study is to present the current situation from a developing country perspective in dealing with such cases at the time of the COVID-19 pandemic. Methods: A cross-sectional analyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
1
0
Order By: Relevance
“…However, the mean cost of these procedures showed an increase ( P = 0.0172) due to limited resources, a lack of specialized neurosurgeons, need for a multidisciplinary team, and challenges maintaining demand for a procedure with a difficult surgical approach. 29 , 30 The cost of craniotomies also varies with patient factors such as age and comorbidities, as well as hospital factors such as teaching hospital status, hospital volume, and geographic region. 31 We believe that we could extend these factors to other neurosurgical procedures, and they likely contributed to an increased mean cost per procedure in our cohort.…”
Section: Discussionmentioning
confidence: 99%
“…However, the mean cost of these procedures showed an increase ( P = 0.0172) due to limited resources, a lack of specialized neurosurgeons, need for a multidisciplinary team, and challenges maintaining demand for a procedure with a difficult surgical approach. 29 , 30 The cost of craniotomies also varies with patient factors such as age and comorbidities, as well as hospital factors such as teaching hospital status, hospital volume, and geographic region. 31 We believe that we could extend these factors to other neurosurgical procedures, and they likely contributed to an increased mean cost per procedure in our cohort.…”
Section: Discussionmentioning
confidence: 99%
“…No viral transmission to the patients and surgical team has been reported in nine cases from Cambridge, United Kingdom. [5] Soliman et al [6] reported no disease transmission in 16 patients, although one surgeon exhibited the symptoms despite a negative PCR test for COVID-19. Finally, in a series of three patients published in the early periods of the pandemic, Penner et al [7] reported no disease transmission in any patient or the members of the surgical team.…”
Section: Postoperative Covid-19 Screeningmentioning
confidence: 99%